A bibliometric Analysis of Biopesticides in Mosquito Control: Current Trends and Future Prospects - Dewi, Mirnawati; Tuju, Fandi; Wanto, Wahyu Anggar (Perkumpulan Entomologi Kesehatan Indonesia, 2025)
Mosquitoes are insects that play a role in the balance of the ecosystem. However, some species of mosquitoes are detrimental because they act as disease carriers (vectors) for humans and animals. The increasing mosquito population is feared to have the potential to become a vector, prompting various efforts to reduce the population, including the use of biopesticides. This article aims to analyze and visualize the research trends on b biopesticides in mosquito control over the past 19 years and to identify potential research topics related to biopesticides for future studies. The methodology used in this article involves a literature review conducted through Publish or Perish and bibliometric analysis using the VOSviewer databases, which collectively encompass 1000 papers. Assessing scientific research progress is crucial for formulating goals and rationalizing future efforts. Based on the results of the bibliometric analysis, biopesticides derived from Bacillus thuringiensis, as well as bacteria, fungi, and other types of microbes, have the potential to be researched and developed as mosquito vector control biopesticide products. Microbial pesticides obtained from actinomycetes, Bacillus thuringiensis (Bt), B. sphaericus (Bs), Lysinibacillus sphaericusand, Saccharopolyspora spinosa, Wolbachia and many other microorganisms are reported as environmentally friendly alternatives for mosquito control.